Pengembangan Game Edukasi Math Hero's Adventure Pada Pembelajaran Matematika Kelas IV Sekolah Dasar - Nina Wulan Nur Fitri; Adin Fauzi; Sripit Widiastuti (Madako Elementary School, 2023)
Learning mathematics in elementary schools has many deficiencies in terms of learning media  so that learning media is needed that can be used so that better learning objectives can be achieved. The purpose of this research is to develop appropiate learning products. This research and development uses Sugyono’s steps with 7 stages of  development, namely: potentials and probelms, data collection, product design, design validation, product revision, product testing, and evaluation. The results of the percentage validation of the 3 validation are: (1) 93,33% of  the ateri experts, (2) 92% of the media experts, and (3) 90,66% of the lingusts. The results of the student readability quwationnaire showed that the Math Hero’s Adventure Education Game was very feasible to use with the  acquisition of a student readability percentage of 96% and the teacher’s readability questionnaire obtaining a percentage 0f 91,5% so. Educational Game Edukasi Matth Hero’s Adventure In Learning Mathematics that is developed can  be used in the learning process.